Differences in cooking taste and physicochemical properties between compound nutritional rice and common rice - Zhang, Dongmeng; Li, Jian; Yao, Dongping; Wu, Jun; Luo, Qiuhong; Shen, Hong; Hu, Meixia; Meng, Fudie; Zhang, Ying; Liu, Xionglun; Shan, Yang; Liu, Dongbo; et al. (Frontiers in Nutrition, 2024)
In this study, it was compared the physicochemical properties and cooking taste quality between four different types of compound nutritional rice (rice flour with the addition of other coarse grains, legumes, potatoes, and other powders, extruded as artificial rice grains) and common rice. We found that the protein and apparent amylose contents of compound nutritional rice were higher than that of common rice, up to 9.775% and 19.45% respectively. The γ-aminobutyric acid (GABA) and resistant starch contents were much lower than in common rice, and the dietary fiber content did not differ from that in common rice. The results of Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis revealed that the starch properties and structure of the compound nutritional rice changed due to high temperature and high pressure processing. In particular, the crystalline structures of starch became V-shaped. In addition, the results of artificial tasting and tasting meter showed that the taste of compound nutritional rice was generally inferior to that of common rice. In summary, compound nutritional rice had problems such as nutritional imbalance and poor taste. There was still a lot of room for improving the taste quality of compound nutritional rice. Therefore, the future development of compound nutritional rice should focus on both nutritional balance and taste improvement. The results of this paper also provided a certain theoretical basis for this.